Demographic and regional trends of sepsis mortality in the United States, 1999–2022 - Reid Morrissey; Joseph Lee; Nikita Baral; Abubakar Tauseef; Akshat Sood; Mohsin Mirza; Ali Bin Abdul Jabbar (BMC Infectious Diseases)
Abstract Sepsis is one of the leading causes of death in the United States. We aimed to explore long term demographic and geographical trends of sepsis-related mortality in the United States from 1999 to 2022. The Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) national database was utilized to analyze differences in mortality associated with sepsis. Age-adjusted mortality rates (AAMR) were calculated, and Joinpoint Regression Program was used to determine trends for mortality. The results demonstrated that 4,177,071 deaths occurred during the study and that mortality increased for most demographic and geographic groups. Sepsis associated mortality did not witness any dramatic change from an AAMR of 77.51 in 1999 to 76.1 in 2019 but saw an increase of 30.22% from 2019 to 2021 which was primarily driven by associated COVID- 19 infections. Demographic and geographical disparities persisted with Men, NH African American and NH American Indians and Alaskan Natives, census region south having worse AAMRs. COVID- 19 contributed to around 1/6 th of sepsis associated deaths in US between 2020 and 2022 and accounted for most of the excess sepsis associated mortality during the pandemic.